Pengaruh Tingkat Kesehatan Bank melalui Metode RGEC terhadap Nilai Perusahaan pada Bank yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Ananda Dwi Maulidiah; Gardina Aulin Nuha; Ibna Kamelia Fiel Afroh (Journal of Trends Economics and Accounting Research, 2025)
The PBV of the banking sector listed on the Indonesia Stock Exchange (IDX) experienced a significant decline from 2020 to 2024. This decline in PBV serves as the basis for this study to gain a deeper understanding of the causes behind the decrease in firm value in the banking sector, as well as to examine the effect of implementing the RGEC method on firm value, which can be applied to help the banking sector maintain profitability amid industry pressures. This study aims to examine the effect of bank health level using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, and Capital) on the firm value of banks listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research covers the banking sector listed on IDX with a total sample of 43 banks over five years of observation, resulting in 215 panel data. The independent variables consist of Non-Performing Loans (NPL), Good Corporate Governance (GCG) proxied by institutional ownership, managerial ownership, and audit committee, Return on Assets (ROA), and Capital Adequacy Ratio (CAR). The dependent variable, firm value, is proxied by Price Book Value (PBV). The analysis method used is multiple linear regression with the assistance of SPSS 26. The results indicate that NPL has a negative and significant effect on firm value. GCG has no significant effect on firm value. Meanwhile, ROA and CAR have positive and significant effects on firm value. These findings suggest that credit risk, profitability, and capital are the main factors influencing the firm value of banks from an investor's perspective.